Avaliação de dor neuropática em pacientes com doença falciforme utilizando o instrumento Douleur Neuropathique 4 Questions (DN4) - Carneiro, Karine Santos Cerqueira (2019)
Patients with sickle cell disease (SCD), in addition to acute vaso-occlusive pain, also develop chronic pain with nociceptive and neuropathic features. The aim of this study was to evaluate the Neuropathic Pain (NP) in patients with SCD using the Douleur Neuropathique 4 Questions (DN4) instrument. A sample of 103 patients was extracted from a total of 554 patients who met the inclusion criteria between 2015 and 2017. DN4 was used for NP detection. Groups with and without NP were compared by sex, age, use of hydroxyurea and sensory alterations by chi-square or Fisher's exact test, ANOVA and Kruskal-Wallis. The mean age was 20.5 years (SD ± 5.1), 32.04% of the patients had NP and 51.5% were male. Most commonly, pain was reported in the back / lumbar region (72.7%). There was an association between age and NP (p <0.05), with a mean of 22.4 years (SD ± 5.2) in the group with NP and 19.6 years (SD ± 4.9) in the group without DN. There was no positive association between NP and hydroxyurea use although most individuals using this medication were in the group without NP. No association was found between absence of NP and absence of sensory changes through the physical examination of the DN4 tool (p = 0.000). Thus, screening for NP can result in faster and more effective diagnoses, contributing to early treatment in view of the impact that pain has on the lives of patients with SCD